PANCASILA DURING THE OLD ORDER, NEW ORDER, AND POST-REFORMATION ERA - Grace Purwo Nugroho; Roby Cahyadi Kurniawan (Jurnal Analisa Sosiologi, 2025)
The current Pancasila has been left unclear and with a vague concept. Historically, the formation of the state foundation in 1945 was marked by a debate on Pancasila that centred on ideological values and social representations of the Indonesian people. A need in the scientific realm and government practice to find out how Pancasila is debated ideologically and whether Pancasila can indeed be practised. The writing of this journal employs a qualitative descriptive method, incorporating a literature review to collect data from previous research, public sources, and credible, legitimate information. The results of the data and information that have been checked for validity are then analysed comprehensively and critically. The findings indicate that the concept of Pancasila encompasses a range of values and ideologies, including those from religion/theology, humanism, nationalism, liberalism, and socialism, all of which are intertwined within the concept of Pancasila. In the practice of the old order state, Pancasila could not be operationalised because the newly established state, the New Order, interpreted it manipulatively for the interests of power and during the reform order, Pancasila experienced degradation. However, the Pancasila study institution, namely BPIP, re-emerged, which became an academic arena for the concept of Pancasila and an opportunity for the operationalisation of Pancasila in the context of government and state.